Investigation of EDM machining parameters of different volume fraction of WC/Ni composites. Issue 1 (December 2020) - Ashokkumar, S; Thiagarajan, C; Jose, Hitheshu; Aswin Murali, P; Jacob, Akhil Reji
Abstract: The main objective of this paper is to analyze the machining and mechanical characteristics of Tungsten carbide/Nickel (WC/Ni) composite materials which are produced through the powder metallurgy route. It also concentrates on various parameters such as Percentage of Nickel composition (%Ni) Electrode rotation (S), Pulse on time (T), Current (C) and Flushing pressure (P), Sliding Speed, Contact Load (N), Time (T)of EDM to investigate the process performance characteristics in terms of material removal rate(MRR) and surface roughness (Ra)and also wear rate. From the experimental results it can be observed that increase % of Ni in Composites (WC/Ni), compositions ((85WC-15Ni), (90WC-10Ni), (95WC-5Ni)) the surface roughness and material removal rate which increases gradually. The above condition is achieved when Pulse on time (T), Current (C) and Flushing pressure (P) maintained at constant values. In addition to that surface roughness was analyzed by using response surface methodology. Comparison of the results of un machined surface of WC/Ni composites with EDMed surface was also performed and the worn-out morphologies of WC/Ni composites were analyzed with the help of Scanning Electron Microscope (SEM).